Virtual Tutoring and Counseling in Schools. (19th July 2012) - Vázquez Cano, Esteban; López Meneses, Eloy
Abstract : This paper is a report on the findings of a study conducted on ten primary and secondary schools in Spain where we evaluated how digital tools can contribute to reinforce and develop new ways of tutoring and counseling. The research shows how many counseling functions can be highly enhanced with the use of virtual tools, that is, academic planning, career postsecondary planning, tutoring, counseling, and personal-social development. One of the most important school counselor's roles is to coordinate resources and services to best assist students and families in fulfilling their needs. Virtual tutoring and counseling through the development of virtual communities are key strategies to better connect with groups—students, parents, administrators, teachers, and others—as part of comprehensive developmental tutoring and counseling programs. Indeed, effective school counseling programs are a collaborative effort among many important groups of people whom digital tools help significantly.